The role of mediation in industrial conflict resolution - Philip, Catharine Mary (Department of Sociology, 2016)
This dissertation analyses the role of industrial mediation within the framework of the relationship between the underlying causes of industrial conflict and the resolution of this conflict. The inextricable relationship between economics and politics means that the underlying causes of industrial conflict need to be located within both the socio-political arena and in the contradictions within the labour process. The Independent Mediation Service of South Africa (IMSSA) has played a crucial role in facilitating the institutionalisation of extra statutory or independent industrial mediation in response to the changing nature of industrial relations in the country. IMSSA is rooted in the pluralist approach to industrial relations. Pluralism is rejected in this dissertation for its implicit acceptance of the existing socio-political status quo and for its belief in the legitimacy of the social system as a fair and democratic one. Thus, a critical question in this research is what is the role of mediation if pluralism is rejected as a starting point for analysis? A distinction is drawn between manifest and latent conflict in this dissertation. The primary hypothesis, which is confirmed, is that mediation addresses the manifest, rather than the latent conflict. This challenges the claim of the problem-solving approach of mediation that the process uncovers the underlying conflict. Instead, this research reveals that mediation is dispute-specific and has the potential for solving the immediate conflict, rather than removing the fundamental sources of this conflict. Further, the role of mediation is limited by the very nature of the collective bargaining process which restricts the expression of the latent conflict. It is argued that, although mediation may be accused of palliating the conflict in the sense that it settles the dispute without addressing the structural causes of the conflict, mediation plays a significant role in the collective bargaining process. This is revealed in the role that mediation plays in improving bargaining skills, empowering the weaker party, legitimising the negotiating parties, educating the parties, overcoming mistrust and promoting understanding between adversaries. Thus, mediation has the potential for significantly affecting the working relationship and altering the dynamics of this relationship in terms of enhancing the essential relationship-building dimension of this relationship and facilitating an approach to bargaining in good faith. The effects of mediation therefore extend beyond the immediate conflict settlement. Mediation is not a response to procedural inadequacies and the utilisation of this process does not reflect inadequate negotiation skills. Instead, the increasing number of industrial mediations may be seen to be a reflection of more sophisticated industrial relations which reveal an acknowledgement of the need to compromise as a prerequisite for successful collective bargaining. Research was conducted and hypotheses tested through primary research which involved interviews with leading management representatives and trade unionists in the Cape Town and Port Elizabeth-Uitenhage regions and mediators in these two areas as well as in Johannesburg and Pretoria. Interviews were conducted oh an open-ended, but structured basis. The two primary regions were chosen for their representation of different trends in the utilisation of industrial mediation. FOcus in the Port Elizabeth-Uitenhage region centred on why mediation has been utilised relatively less frequently in this region than elsewhere in the country. It was found that, although specific forces have shaped the unique nature of collective bargaining in this region, the attitude towards mediation arose not from more militant or confrontational policies, but from a number of misperceptions and faulty assumptions concerning the process and role of mediation.